If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(x + -1) = 5x + 4 Reorder the terms: 3(-1 + x) = 5x + 4 (-1 * 3 + x * 3) = 5x + 4 (-3 + 3x) = 5x + 4 Reorder the terms: -3 + 3x = 4 + 5x Solving -3 + 3x = 4 + 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. -3 + 3x + -5x = 4 + 5x + -5x Combine like terms: 3x + -5x = -2x -3 + -2x = 4 + 5x + -5x Combine like terms: 5x + -5x = 0 -3 + -2x = 4 + 0 -3 + -2x = 4 Add '3' to each side of the equation. -3 + 3 + -2x = 4 + 3 Combine like terms: -3 + 3 = 0 0 + -2x = 4 + 3 -2x = 4 + 3 Combine like terms: 4 + 3 = 7 -2x = 7 Divide each side by '-2'. x = -3.5 Simplifying x = -3.5
| 2x-k=-1 | | X-5=2(x-20) | | 5.65-.05q=.75+.0125q | | 2-3(2)=-7 | | 10w-20=3w-36 | | 2-3(-4)=-7 | | 7+3*n=5 | | 7t+25=8+16(t+3) | | p+20=2p-17 | | 5cos^2x+2=3 | | 4/5.5/4.-3= | | 25-2b=9 | | 20c-18=14c | | -2(5s-5)-10=-2(9s+10)-3 | | 3c=2c+17 | | s-2=5-s | | Y=-0.02x^2+.5x | | 7q+2(3-2w)=4(w+2)-(w-6) | | 2(4-4)+32= | | 2y=3y-13 | | 5(y-2)-2=(y+1)-5 | | 97/5-x/5=2.6 | | 6a=a+5 | | 2.5x=-20 | | 12x+3=8x+43 | | 18u+3=10u | | -39=1-5(-7) | | 4x-5y-5=0 | | 14d=10d+12 | | 8x+y=177 | | 97-x/5=2.6 | | Y=-0.02x^2+.5 |